Resistência ao desgaste, corrosão e sinergia do aço duplex UNS S32205 com e sem nitretação a plasma em baixa temperatura - Rosa, Yamid Enrique Núñez de la (2018)
Duplex stainless steels have good resistance to wear and corrosion and are therefore applied in the food, chemical and petrochemical sectors. In the latter, various components such as risers, valves, shafts, propellers, rings are duplex steel pipes that are used in the transportation of petroleum, working in aggressive conditions, in the presence of abrasive particles and chloride ions, which together create an environment in which this steel can become brittle due to its degradation. In order to improve the resistance of these stainless steels, it was proposed the introduction of nitrogen by the thermochemical treatment of low temperature (380°C) plasma nitriding performed in GrMaTS / UTFPR. The thermochemical treatment was carried out in a reactor containing N2-H2 atmosphere for a time of 10 h, with previous cleaning treatment and heating with Ar-H2. In this work, with the objective of evaluating the relationship between the plasma nitriding of the UNS S32205 series duplex steel in the synergism that occurs due to wear and corrosion, isolated tests of pure abrasion (without corrosion) were carried out in an atmosphere environment controlled inside a closed box type glove box by means of a free ball type tribometer. The pure corrosion tests (without abrasion) were carried out in 3.5% NaCl solution in a potentiostat assisted electrochemical cell from the potentiodynamic polarization technique. Subsequently, the strength of this material was evaluated for tribocorrosion containing a combination of wear test and an electrolytic medium to promote corrosion. Subsequently, the characterization of the surface was carried out using optical microscopy (OM), X-ray diffraction (XRD), scanning electron spectroscopy (SEM-EDS) and Vickers microhardness tests. The treatment of plasma nitriding promoted the formation of the metastable phase of expanded austenite with a thickness of 3.0 ± 0.2 μm and a hardness of 1101.8 ± 179.9 HV0.05. It was noticed that nitrided steel was improved because it presented less resistance to transfer and greater potential of pite, greater resistance to pure wear, and verified that in the tribocorrosive test that the mechanical and electrochemical processes interact with each other to increase the overall wear process of materials. and finally that the magnitude of the synergism foreach of the study materials is implicitly related to the aggressiveness of the effect of the medium on the material.